Conditions for the Great Religion Singularity - McLaren, Brian D. 1956- (2019)
Applying the Buddhist “law of interdependent origination,” which states that if the conditions are right, a particular phenomenon may exist, Brian McLaren provides ten conditional factors that he believes have contributed to Ken Howard’s “religion singularity” (i.e. the multi-faceted collapse of institutional Christianity). Each condition falls under two main categories: either a lack of rapid adaptability in religious institutions or the moral failure of institutional leaders. The ten conditional factors include authoritarian centralization, betrayal of the religious founder’s non-violence, a history of unacknowledged atrocities, military imperialism, white supremacy, scandals, reaction against scientific inquiry, doubling down on dualism, integrated and change-averse institutional systems, and paralysis and nostalgia.